A general survey of the principles of determining the ratio of specific charge to inertial mass of an electron with special reference to and experimental verification of the work of Sir J.J. Thomson on cathode rays - De Villiers, G. D. B.(Gabriel Daniel Bosman) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1934.